Chemical composition and cytotoxic activity of the essential oils of Cymbopogon citratus L. Grown in phu tho province - Van, Hoang Thi Kim; Quy, Nguyen Minh; Ha, Do Thi Vinh; Hai, Nguyen Thanh; Ly, Hoang Thi; Hien, Nguyen Thi; Trang, Duong Thu; Dang, Nguyen Hai; Dat, Nguyen Tien (Vietnam Journal of Biotechnology, 2018)
Culms and leaves of Cymbopogon citratus L. were collected from two regions of Phu Tho province (Thanh Son and Phu Ninh) and used as materials for essential oil extraction. Oils obtained were steam-distilled, analyzed for chemical composition and evaluated for cytotoxic activity against three different cancer cell lines. The GC/MS analysis showed that citral is the major content of the steam-distilled essential oils which was found in the range of 64.15-76.22%. Camphene was found only in culm oils of both regions but it was not detected in the leaf oils. Interestingly, the isomer forms of ocimene present at higher content in the culm oils than in the leaf oils whereas myrcene content in the leaf oils is higher than that in the culm oils. In a cytotoxicity test, four essential oils of culms and leaves of C. citratus from Thanh Son and Phu Ninh showed potent activity against A549 (human lung carcinoma) cell line with the IC50 values ranging from 4.01±0.39 to 6.3±0.54 µg/ml. The essential oils (culms and leaves) from Phu Ninh exhibited moderate effects on the Hela (human cervical adenocarcinoma) cells with the IC50 values of 19.43±1.16 and 42±2.41 µg/ml, respectively. However, they were inactive against the human hepatocellular carcinoma Hep3B cell line. The essential oils from Thanh Son exhibited potent cytotoxic activity against Hela and Hep3B cell lines with the IC50 values ranging from 1.18±0.26 to 8.91±0.32 µg/ml. The results indicated that the essential oils of C. citratus from Thanh Son, Phu Tho could be considered as a promising candidate for the natural sources of anticancer agents